FAKTOR - FAKTOR YANG MEMPENGARUHI DERAJAT MIOPIA ANAK USIA SEKOLAH PADA PASIEN OPTIK RIZ-Q - Abdul Azis Al Anwar; Ferry Doringin; Murni Marlina Simarmata (Jurnal Mata Optik, 2021)
This study was aimed at deciding risk factors of myopia suffered by school children and at finding out important prevention in order to eliminate the risk. The research was conducted in Riz-Q optical, located at Kembangan, West Jakarta. Employing qualitative method, the research collected data from children of Riz-Q optical customers suffering from myopia. The samples were school kids (15-19 years old) who were students of grade X-XII Senior High School. Findings of this study comfirm: (1) parents genetic significantly effects children prevalence to myopia; (2) behavior in using gadget, i.e., distance to eye, duration of use, body position when using gadget and low intensity of room as well as the lack of A and B vitamins usually derivating from food and sun light, significantly boost prevalence to myopia.